Single-sex schistosomiasis: a mini review - Zhong, Haoran; Jin, Yamei (Frontiers in Immunology, 2023)
Schistosomiasis is a neglected tropical disease caused by dioecious blood flukes of the genus Schistosoma and second to malaria as a parasitic disease with significant socio-economic impacts. Mating is essential for maturation of male and female schistosomes and for females to lay of eggs, which are responsible for the occurrence and spread of schistosomiasis. Single-sex schistosomes, which cannot produce normal eggs without mating, are overlooked because of the lack of obvious clinical symptoms and limited specialized detection methods. Besides, single-sex schistosomes are less sensitive to praziquantel. Therefore, these issues must be addressed to eliminate schistosomiasis. The aim of this review is to summarize current progress in research of single-sex schistosomes and host-parasite interactions.